Managing cardiovascular events, hyperglycemia, and obesity in type 2 diabetes through microRNA regulation linked to glucagon-like peptide-1 receptor agonists - Xiaolei Miao; Maryam Davoudi; Zahra Alitotonchi; Ensieh Sadat Ahmadi; Fatemeh Amraee; Ashraf Alemi; Reza Afrisham (Diabetology & Metabolic Syndrome)
Abstract Background and aims Type 2 diabetes mellitus (T2DM) is usually complicated by cardiovascular diseases, hyperglycemia, and obesity, which worsen the outcome for the patient. Since recent evidence underlines the epigenetic role of glucagon-like peptide-1 receptor agonists (GLP-1RAs) in the management of these comorbidities, this study compared the effects of these agents, namely liraglutide, semaglutide, dulaglutide, and exenatide, on miRNA regulation in the management of T2DM. Results GLP-1RAs modify the expression of miRNAs involved in endothelial function, sugar metabolism, and adipogenesis, including but not limited to miR-27b, miR-130a, and miR-210. Baseline miR-15a-5p predict weight loss, while higher miR-378-3p and miR-126-3p levels are related to better glycemic control and lower HbA1c and FPG at one year post-treatment. miR-375-5p was also reported as a predictor of HbA1c levels. Liraglutide has a protecting effect against pancreatic β-cell apoptosis by downregulating miR-139-5p. The highly-expressed miR-375 in pancreatic islets can be considered as a biomarker for assessing the cytoprotective action of GLP-1RAs on β-cells. GLP-1RAs also enhance β-cell responsiveness by promoting GLP-1 receptor expression through the suppression of miR-204. While semaglutide, semaglutide, and dulaglutide reduce both systolic and diastolic blood pressures, lixisenatide and exenatide QW did not reveal such an effect. The long-acting exenatide-induced miR-29b-3p is required for the protection against diabetic cardiomyopathy. Liraglutide modulates critical regulators of endothelial cell function and atherosclerosis, including miR-93-5p, miR-26a-5p, and miR-181a-5p. Eventually, GLP-1RAs regulation of exosomal miRNAs, such as miR-192, implicated in the development of fibrosis and inflammation in T2DM micro-cardiovascular outcomes like DKD and DR. Conclusion Additional studies will be needed in the elucidation of the relations between GLP-1RA-induced miRNAs and clinical-laboratory findings concerning the diverse populations, gender, and presence of other comorbid states in treated patients with T2DM.